1998
DOI: 10.1128/aac.42.7.1738
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein-Mediated Transport of Itraconazole across the Blood-Brain Barrier

Abstract: The mechanism for the accumulation of itraconazole (ITZ) in its elimination from the brain was studied in rats and mice. The concentration of ITZ in liver tissue declined in parallel with the plasma ITZ concentration until 24 h after intravenous injection of the drug (half-life, 5 h); however, the ITZ in brain tissue rapidly disappeared (half-life, 0.4 h). The time profiles of the brain/plasma ITZ concentration ratio (Kp value) showed a marked overshooting, and the Kp valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 30 publications
4
42
1
1
Order By: Relevance
“…The V max1 and V max2 for vinblastine uptake by RBMVECs were 7.37 T 1.16 and 3.11 T 0.21 ng/min/mg cellular protein, respectively. These results are comparable to those reported in the literature (43,44). We also monitored the intracellular concentration of glabridin at 1.0 mM upon incubation over 120 min (Fig.…”
Section: Intracellular Accumulation and Efflux Of Glabridin In Rat Brsupporting
confidence: 89%
“…The V max1 and V max2 for vinblastine uptake by RBMVECs were 7.37 T 1.16 and 3.11 T 0.21 ng/min/mg cellular protein, respectively. These results are comparable to those reported in the literature (43,44). We also monitored the intracellular concentration of glabridin at 1.0 mM upon incubation over 120 min (Fig.…”
Section: Intracellular Accumulation and Efflux Of Glabridin In Rat Brsupporting
confidence: 89%
“…4). Since it has been reported that ITCZ is an inhibitor of P-glycoprotein, 13 and that the inhibition of P-glycoprotein enhances the cytotoxicity of VCR in leukemic cells, 14 this enhanced VCR activity may be explained by the possible accumulation of VCR in the cells, resulting from P-glycoprotein inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…One reason could be a low permeation of itraconazole across the blood brain barrier (BBB) after its oral administration, which was already observed in vivo with rats and mice using itraconazole capsules containing polyethylene glycol (Perfect et al, 1986). Another reason for therapeutic failures in cryptococcal meningitis could be the rapid transport of itraconazole out of the brain as shown in a study in which itraconazole was administered intravenously in a polyethylene glycol-containing solution (Miyama et al, 1998). Miyama et al suggested that itraconazole is a substrate for multi-drug resistance gene P-glycoprotein expressed in the mouse brain endothelial cells and may be a cause for rapid efflux of itraconazole from the brain tissue.…”
Section: Introductionmentioning
confidence: 92%